2002
DOI: 10.1046/j.1469-8137.2002.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Function of epidermal surfaces in the trapping efficiency of Nepenthes alata pitchers

Abstract: Summary Several epidermal microstructures characterize surfaces of pitcher plants and are presumably involved in their trapping function. Here we report the effects of Nepenthes alata surfaces on insect locomotion and trapping efficiency. The architectural designs of pitcher surfaces were characterized using scanning electron microscopy. Two insect species – fruitfly (Drosophila melanogaster) and ant (Iridomyrmex humilis) – were tested for their ability to remain and walk on them. The relative contributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
149
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(154 citation statements)
references
References 31 publications
(35 reference statements)
4
149
1
Order By: Relevance
“…The extreme temporal variation of pitcher capture efficiency has not been documented previously. It explains why the trapping function of the peristome has long remained overlooked (Lloyd 1942;Juniper et al 1989;Gaume et al 2002). Why should a carnivorous plant have evolved a trapping mechanism which is often ineffective and thus seemingly ill designed?…”
Section: Discussion (A) Activation Of Traps By Peristome Wettingmentioning
confidence: 99%
“…The extreme temporal variation of pitcher capture efficiency has not been documented previously. It explains why the trapping function of the peristome has long remained overlooked (Lloyd 1942;Juniper et al 1989;Gaume et al 2002). Why should a carnivorous plant have evolved a trapping mechanism which is often ineffective and thus seemingly ill designed?…”
Section: Discussion (A) Activation Of Traps By Peristome Wettingmentioning
confidence: 99%
“…Excellent attachment ability on various smooth artificial and natural surfaces has been previously reported for many insects (Way and Murdie 1965;Stork 1980;Edwards 1982;Eigenbrode 1996;Federle et al 2000;Gorb 2002, 2006a). In waxy plant substrates, the deteriorative effect of the crystalline wax coverage on insect attachment has been experimentally shown by many authors (Stork 1980(Stork , 1986Edwards 1982;Bodnaryk 1992;Eigenbrode 1996;Eigenbrode et al 2000;Federle et al 2000;Eigenbrode and Jetter 2002;Gaume et al 2002Gaume et al , 2004Gorb et al 2005;Voigt et al 2007). It has been found for several insect species and a series of plant species that insects can attach well to smooth substrates, without wax or with removed wax bloom, whereas they fail on waxy surfaces.…”
Section: Wax-mediated Beetle Attachmentmentioning
confidence: 95%
“…Regarding the latter function, it has been previously repeatedly reported that plant surfaces, bearing crystalline wax coverage, reduce the attachment of insects (Stork 1980(Stork , 1986Edwards 1982;Bodnaryk 1992;Eigenbrode 1996;Eigenbrode et al 2000;Federle et al 2000;Eigenbrode and Jetter 2002;Gaume et al 2002Gaume et al , 2004Gorb et al 2005;Voigt et al 2007). In some of these studies, conducted with different insect and plant species, it has been experimentally shown that insects were able to attach successfully to smooth substrates, without wax or with removed wax, but failed on pruinose surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The numerous studies on the function of Nepenthes pitchers have focused on the mechanism of insect attraction (6,7), on the trapping of insects by alkaloid anesthesia (8), by slippery epicuticular wax crystals (3,5,9,10) or by downwardpointing lunate cells (3) of the inner pitcher wall, on the properties of the glandular zone (11), and on the nature of the digestive fluid (12)(13)(14). Only recently, L. Gaume et al (15) conducted the first comprehensive study on the trapping mechanism of Nepenthes by comparing the effect of the different pitcher surface zones and by separating the mechanisms of prey capture and retention. Observations of insects placed on Nepenthes alata pitchers suggested that the inner waxy pitcher wall is the most important surface zone for the initial capture of insects (15).…”
mentioning
confidence: 99%
“…Only recently, L. Gaume et al (15) conducted the first comprehensive study on the trapping mechanism of Nepenthes by comparing the effect of the different pitcher surface zones and by separating the mechanisms of prey capture and retention. Observations of insects placed on Nepenthes alata pitchers suggested that the inner waxy pitcher wall is the most important surface zone for the initial capture of insects (15). These results confirmed earlier observations that insects are trapped when they step on the waxy zone while visiting the nectaries on the inner side of the pitcher rim (peristome) (e.g., refs.…”
mentioning
confidence: 99%